Ischemic Stroke in a Young Patient with Nephrotic Syndrome and Antiphospholipid Syndrome - K. K. Neoh; A. S. N. Tang; I. Looi; B. M. Anita (Case Reports in Nephrology)
We report a case of a 21-year-old man with underlying nephrotic syndrome (NS) secondary to minimal change disease, who developed an ischemic stroke with left hemiparesis. He received intravenous thrombolysis followed by a mechanical thrombectomy. After mechanical thrombectomy, he developed acute kidney injury which subsequently required haemodialysis. Further workup revealed that he had concomitant antiphospholipid syndrome (APS) and NS. He was started on vitamin K antagonist anticoagulant. This case report illustrates the importance of workup in identifying causes of ischemic stroke in a young patient.